STRATEGI PEMASARAN PRODUK TABUNGAN iB HIJRAH HAJI PADA BANK MUAMALAT KANTOR CABANG PEMBANTU BANDAR LAMPUNG DI MASA PANDEMI COVID-19 - Robiyah Nur (Institut Agama Islam Negeri Metro, 2022)
Abstract: The iB Hijrah Haji Muamalat Savings Product for Bandar Lampung Sub-Branch Office is a superior product that has many enthusiasts compared to other products. Bank Muamalat Indonesia creates Hajj products and is always vigilant in marketing strategies. The purpose of this study was to examine the marketing strategy carried out by the iB Hijrah Haji savings product bank at Bank Muamalat Bandar Lampung Sub-Branch Office during the covid-19 pandemic. The type of research used in this research is field research (field research). This study uses an approach approach, and in data collection using observation, interviews, and documentation. The results of this study indicate that the marketing strategy of the iB Hijrah Haji savings product during the covid-19 pandemic has the effect of increasing the number of customers, making it easier for the public and new customers to get about the Hijrah Haji savings product, increasing public knowledge and increasing the reputation of Bank Muamalat, Bandar Lampung Sub-Branch Office.